The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12640-017-9802-1
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to the Cyanotoxin β-N-Méthylamino-l-Alanine (BMAA) Results in Long-Lasting Behavioral Changes in Offspring—Potential Involvement of DNA Damage and Oxidative Stress

Abstract: We recently demonstrated that perinatal exposure to the glutamate-related herbicide, glufosinate ammonium, has deleterious effects on neural stem cell (NSC) homeostasis within the sub-ventricular zone (SVZ), probably leading to ASD-like symptoms in offspring later in life. In the present study, we aimed to investigate whether perinatal exposure to another glutamate-related toxicant, the cyanobacterial amino acid β-N-methylamino-L-alanine (BMAA), might also trigger neurodevelopmental disturbances. With this aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…It is a common neurotoxin utilized in the study of neurodegeneration in cellular and animal models, specifically those for the study of ALS/Parkinsonism-dementia complex. BMAA causes neuroinflammation, oxidative stress, apoptosis and cognitive impairment (Brownson et al, 2002; Lobner, 2009; Santucci et al, 2009; Zhou et al, 2010; Muñoz-Saez et al, 2013; Al-Sammak et al, 2015; Takser et al, 2016; Laugeray et al, 2017; Petrozziello et al, 2017). It elicits neurotoxicity by acting as an agonist for glutamate receptors such as AMPARs/KARs, NMDARs, and mGluR5 (Lobner, 2009; Delzor et al, 2014).…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%
“…It is a common neurotoxin utilized in the study of neurodegeneration in cellular and animal models, specifically those for the study of ALS/Parkinsonism-dementia complex. BMAA causes neuroinflammation, oxidative stress, apoptosis and cognitive impairment (Brownson et al, 2002; Lobner, 2009; Santucci et al, 2009; Zhou et al, 2010; Muñoz-Saez et al, 2013; Al-Sammak et al, 2015; Takser et al, 2016; Laugeray et al, 2017; Petrozziello et al, 2017). It elicits neurotoxicity by acting as an agonist for glutamate receptors such as AMPARs/KARs, NMDARs, and mGluR5 (Lobner, 2009; Delzor et al, 2014).…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%
“…It is widely accepted that the developing brain is more sensitive to the harmful effects of environmental contaminants than the adult brain 36 . It is important to mechanistically elucidate BMAA's effects on the developing brain, as this toxin has been detected in water and food chains all over the world 3739 , and is shown to adversely affect the immature brain 25,27,40–42 . The present study revealed different susceptibilities of primary striatal neurons and NSC to BMAA-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory environment in ALS changes with disease progression. Resident glial cells and infiltrating immune cells are considered among the major producers of ROS and reactive nitrogen species, which contribute to the pathological conditions of the CNS, including phagocytosis and apoptosis of the spinal cord motor neurons and neurons in the dentate gyrus (DG) region of the hippocampus [6,8,29]. The Alzheimer’s disease-like pathology is synergistic and dependent on oxidative stress and inflammation; thus, administration of anti-inflammatory agents might alleviate the disease outcome [30].…”
Section: Discussionmentioning
confidence: 99%